Evaluasi Desain Sistem Informasi Sifasum Pada Manajemen Peminjaman Sarana Prasarana Di Universitas Islam Negeri Sunan Ampel Surabaya - Saputri, Nurdiana (JUSS (Jurnal Sains dan Sistem Informasi), 2025)
Abstract In general, the utilization of Information Systems in the field of Virtual office (VO) in the State Islamic University (UIN) in Sunan Ampel Surabaya is not optimal and has not shown the direction of developing an Information System in the VO field, and has not been supported by an effective management system and work processes. the absence of a strategic plan in the development of an Information System. This study, aimed at analyzing and evaluating the evolving Information System in the field of VO at Sunan Ampel Surabaya UIN called Sifasum, this system still needs to be developed, starting from the display of less interactive interfaces, to features that have not functioned optimally. This study uses a method of evaluating Sifasum's performance on its appearance and features. So based on this evaluation, Sunan Ampel Surabaya UIN must develop an Information System Strategic Plan that is adapted to the conditions and needs of Sifasum development, both in terms of governance and applicable standards, as well as the appearance of the Interface.